Bilateralne razlike različnih tipov košarkaric v odrivni moči - Kambič, Tim (Šport (Ljubljana), 2016)
Basketball is a sport where success is largely dependent on explosive power, which is differed by playing position according to muliple studies. Training process can lead to many differences in strength and power of muscles of the lower limbs, which can lead to a number of injuries and decline in performance. This aim of this study was to evaluate the possible differences in the bilateral take off power with three different vertical jump tests according to the playing position. 19 basketball players from women's basketball club Grosuplje and Triglav participated in this study with mulityear playing experiences nationally and abroad. Among them were 8 guard, 6 forwards and 4 centers. Average age was 21.39 +- 3.05 years, height 176.61 +- 5.83 cm and weight 69.72 +- 7.18 kg. The results were collected by bilateral force plate and program ARS. We have found that in all three jump tests there were no significant difference in the measured take off parameters according to the playing position. Greatest differences were found in majority of the measured parameters between guards and centers. We suggest that in training process more time should be dedicated to learning the proper technique of jumps and to systematic development of explosive power, which should be accompanied by regular measurements of explosive power on the bilateral force plate.
Keywords: basketball; bilateral differences; bilateralne razlike; košarka; odrivna moč; sport; šport; take-off power; tensiography; tenziografija; women; ženske